2014
DOI: 10.1016/j.ultsonch.2014.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Role of H2O2 in the fluctuating patterns of COD (chemical oxygen demand) during the treatment of palm oil mill effluent (POME) using pilot scale triple frequency ultrasound cavitation reactor

Abstract: Palm oil mill effluent (POME) is a highly contaminating wastewater due to its high chemical oxygen demand (COD) and biochemical oxygen demand (BOD). Conventional treatment methods require longer residence time (10-15 days) and higher operating cost. Owing to this, finding a suitable and efficient method for the treatment of POME is crucial. In this investigation, ultrasound cavitation technology has been used as an alternative technique to treat POME. Cavitation is the phenomenon of formation, growth and colla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…They concluded that longer sonication time presents better COD removal in a short period of time. Manickam et al [225] examined the effect of combined ultrasonic bath and hexagonal ultrasonic reactor. The experiment was conducted at a varied frequency of 28, 40, and 70 kHz, and they concluded that the combined effect presents consistent COD degradation.…”
Section: Sonication Processes In Mbr (Sonmbr)mentioning
confidence: 99%
“…They concluded that longer sonication time presents better COD removal in a short period of time. Manickam et al [225] examined the effect of combined ultrasonic bath and hexagonal ultrasonic reactor. The experiment was conducted at a varied frequency of 28, 40, and 70 kHz, and they concluded that the combined effect presents consistent COD degradation.…”
Section: Sonication Processes In Mbr (Sonmbr)mentioning
confidence: 99%
“…As above mentioned, US can be coupled with other AOPs (e.g., photochemical systems) to increase degradation effects. However, large scale US processing is currently limited [33] , [34] , [35] .…”
Section: Introductionmentioning
confidence: 99%
“…Higher substrate concentrations presented lower removal efficiency. This response reduction may be due to the mineralization of components present in POME into H 2 O and CO 2 , while the increase in COD removal could be due to the formation of simple intermediates gained from the conversion of complex components in POME . At the three reaction temperatures (30, 35, and 40 °C) there was no significant COD removal difference, and the range was <10% at each incubation time .…”
Section: Resultsmentioning
confidence: 92%